Workplace team resilience: A systematic review and conceptual development. (August 2020) - Hartwig, Angelique; Clarke, Sharon; Johnson, Sheena; Willis, Sara
Workplace team resilience has been proposed as a potential asset for work teams to maintain performance in the face of adverse events. Nonetheless, the research on team resilience has been conceptually and methodologically inconsistent. Taking a multilevel perspective, we present an integrative review of the workplace team resilience literature to identify the conceptual nature of team resilience and its unique value over and above personal resilience as well as other team concepts. We advance resilience research by providing a new multilevel model of team resilience that offers conceptual clarification regarding the relationship between individual-level and team-level resilience. The results of our review may form the basis for the development of a common operationalization of team resilience, which facilitates new empirical research examining ways that teams can improve their adversity management in the workplace.